Command Line Fundamentals : Learn to Use the Unix Command-Line Tools and Bash Shell Scripting. - N, Vivek (Packt Publishing Ltd, 2018)
From the bash shell to the traditional UNIX programs, and from redirection and pipes to automating tasks, Command Line Fundamentals teaches you all you need to know about how command lines work.